Peningkatan Budaya Literasi Dan Pemanfaatan Perkembangan Teknologi Dalam Berbagai Aspek Kehidupan - Rizky Febriansyah; Elisabeth Michelle Levine Natasha; Emi Febrina Depari; Fatima Nur Ramadhani; Fikri Humaidi; Lasma Rito Sitanggang; Rendi Matius Widjaya; Sintia Selfiana Sinaga; Sri Okta Sema; Willi Wilson M Hutabarat (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The problem that is rife today is the lack of interest in reading in children. Indonesia's literacy index in the world according to the 2018 PISA survey Indonesia is at number 74 out of 79 or six ranks from the bottom. This is very concerning for the Indonesian state. The University of Riau real work group in Suka Maju Village did the service there, based on the fact that there was a lack of literacy in school children which made them less interested in reading and slow in understanding, this happened due to the lack of support for environmental factors there. Based on this incident, the real work college group created a work program that could increase the literacy of school children. To increase village potential, efforts are made through social media accounts as appropriate technology. The activities carried out start from preparation by planning the activities to be carried out. Lessons are held 3 days a week and as a result they become more interested in studying and reading to explore the material that has been taught.